2021
DOI: 10.3390/vaccines9121467
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Immunisation, Willingness to Be Vaccinated and Vaccination Strategies to Improve Vaccine Uptake in Australia

Abstract: The COVID-19 vaccine rollout is crucial to lifting community and economic restrictions. This cross-sectional study aimed to assess: (a) COVID-19 vaccine uptake and associated factors; (b) COVID-19 vaccine intentions and associated factors; (c) community support for COVID-19 vaccination strategies and associated factors. The survey was conducted between May and July 2021 in Australia. Of 3003 participants, 30% reported they were already vaccinated and 39% indicated they would get vaccinated. Low socioeconomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…The deprivation index is a multidimensional index that considers and combines several socioeconomic factors, including educational level. Several studies have confirmed that education significantly influences the willingness to accept vaccination, as those with lower education are more likely to refuse COVID-19 vaccination [ 49 , 50 , 51 , 52 , 53 ]. Since education is one of the most important (if not the most important) determinants of the deprivation index [ 20 ], it is assumed that higher education and the related higher willingness to accept vaccination may be a decisive factor for the higher vaccination coverage identified in more advantaged socioeconomic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The deprivation index is a multidimensional index that considers and combines several socioeconomic factors, including educational level. Several studies have confirmed that education significantly influences the willingness to accept vaccination, as those with lower education are more likely to refuse COVID-19 vaccination [ 49 , 50 , 51 , 52 , 53 ]. Since education is one of the most important (if not the most important) determinants of the deprivation index [ 20 ], it is assumed that higher education and the related higher willingness to accept vaccination may be a decisive factor for the higher vaccination coverage identified in more advantaged socioeconomic areas.…”
Section: Discussionmentioning
confidence: 99%
“…No matter what, campaigns aiming to mitigate vaccine hesitancy should to a larger degree address social and cultural aspects in addition to economic ones, which policymakers already have paid attention to when offering vaccination without user payments and even offering economic incentives such as high-stake lotteries. The need for a nuanced view of vaccine hesitancy for developing tailored communication and mitigation campaigns is widely recognized in diverse contexts including, but not limited to, Australia ( Wang et al, 2021 ), Italy ( Moscardino et al, 2022 ), and Africa ( Mutombo et al, 2022 ). This notwithstanding, so far, only a few countries have transcended a focus on simple started tailoring their campaigns to specific population segments such as culturally-defined groups ( Rosen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An online survey found a higher proportion of parents refused vaccination for their child than the proportion of adults who refused COVID-19 vaccination for themselves. 75…”
Section: Discussionmentioning
confidence: 99%
“…An online survey found a higher proportion of parents refused vaccination for their child than the proportion of adults who refused COVID-19 vaccination for themselves. 75 Since current mRNA vaccines do not prevent infection or transmission with the Omicron variant, further studies are needed on variant-specific mRNA vaccines and other vaccine platforms. Vaccines with a potential to prevent infection in addition to severe COVID-19 could help reduce community transmission and provide population protection as with the nasal influenza vaccines for children.…”
Section: Discussionmentioning
confidence: 99%